Engineering the Ligand Specificity of the Human Galectin‐1 by Incorporation of Tryptophan Analogues. (19th January 2022) - Tobola, Felix; Lepšík, Martin; Zia, Syeda Rehana; Leffler, Hakon; Nilsson, Ulf J.; Blixt, Ola; Imberty, Anne; Wiltschi, Birgit
Abstract: Galectin‐1 is a β‐galactoside‐binding lectin with manifold biological functions. A single tryptophan residue (W68) in its carbohydrate binding site plays a major role in ligand binding and is highly conserved among galectins. To fine tune galectin‐1 specificity, we introduced several non‐canonical tryptophan analogues at this position of human galectin‐1 and analyzed the resulting variants using glycan microarrays. Two variants containing 7‐azatryptophan and 7‐fluorotryptophan showed a reduced affinity for 3'‐sulfated oligosaccharides. Their interaction with different ligands was further analyzed by fluorescence polarization competition assay. Using molecular modeling we provide structural clues that the change in affinities comes from modulated interactions and solvation patterns. Thus, we show that the introduction of subtle atomic mutations in the ligand binding site of galectin‐1 is an attractive approach for fine‐tuning its interactions with different ligands. Abstract : Tryptophan analogues tailor lectin specificity : Atomic mutations introduced at the single tryptophan residue in the galectin‐1 carbohydrate binding site reduce the affinity for selected, sulfated ligands without substantially affecting the interaction with other sugars. Molecular modeling traces this change in affinity back to altered solvation patterns, modulated CH‐π interactions, and electrostatic repulsion between the sulfated ligands and the introduced fluorine as well as nitrogen atoms.